A digital therapeutic for management of psychosocial aspects of psoriasis: A pre‐post proof of concept study. Issue 2 (5th April 2022) - Fortune, D. G.; Ravnkilde, V.; Ryan, S.; Ramsay, B.; Clough, S.; Richards, H. L.
Abstract: Background: Despite the psychosocial challenges of living with psoriasis many patients may not be able to access appropriate services to manage these challenges. Mobile health interventions may be helpful as a means to support patients in managing the impact of their condition. Objective: To conduct a preliminary examination of the feasibility and acceptability of a bespoke psoriasis‐specific digital therapeutic solution (hereafter termed Allay ), and to provide initial data on psychological changes pre‐post. Methods: Phase one proof of concept pre‐post study. Eligible patients were provided with Allay on their smartphone and assessed at baseline and at 12 weeks on a range of indices of well‐being. Participants experiences on usability were collected by telephone interview at 4 weeks, 8 and 12 weeks. Results: Out of 66 participants recruited, 59 persisted in using Allay after the familiarisation phase, and 34 participants completed the 12 weeks programme. Participants showed a statistically significant improvement between induction and the end of the 12 weeks programme on Quality of life, Resilience, Perceptions of 'Overall impact' of psoriasis, and 'Emotional impact'. There was a significant change over the course of using Allay for symptoms of depression but not anxiety. While there was an interaction effect of changes in severity of psoriasis symptoms over the course of the study for dermatology‐specific measures, there was no interaction between such changes in psoriasis symptoms and changes in depression, resilience or beliefs in emotional impact. Conclusions: Study results suggest that the use of Allay as an adjunct to medical management of psoriasis may help patients improve resilience, mood, beliefs about their condition and enhance their quality of life. Given that this is a phase one proof of concept study, and our rates of attrition further research is necessary to examine comparative effectiveness and stability of these findings. Abstract :